The representation of religious values in Malay poetry in West Kalimantan - Ramadhan Kusuma Yuda; Sarwiji Suwandi; Nugraheni Eko Wardani (Research Journal in Advanced Humanities, 2024)
West Kalimantan is a border region between Indonesia and Malaysia. Most of the population in Kalimantan consists of the Malay and Dayak ethnic groups. The Malay people have a highly diverse culture, and one of their cultural expressions is syair (Malay poetry). This research aimed to describe the religious values represented in Malay poetry in Ketapang, West Kalimantan. Thus, the researcher employed an ethnographic approach. Data were collected through observation and interviews. The study was conducted in Ketapang region. The findings indicated that the religious values in syair in Ketapang consisted of 25 about beliefs (aqidah), 71 about Islamic laws (syariah), 31 about ethics (akhlaq), 6 about Islamic principles, 17 about faith (iman), and 50 about good deeds (ihsan). These results have positive implications for syair in the Malay community in Ketapang, ensuring that it is recognized and continues to thrive. This research can be a reference source for learning religious values-based literature in the schools and has benefits as an effort to preserve syair in West Kalimantan.